2020
DOI: 10.1002/anie.202011322
|View full text |Cite
|
Sign up to set email alerts
|

Umpolung of B−H Bonds by Metal–Ligand Cooperation with Cyclopentadienone Iridium Complexes

Abstract: In contrast to conventional metal–ligand cooperative cleavage of a B−H bond, which provides a B cation on the ligand and an H anion on the metal, we report herein the umpolung of B−H bonds by novel cyclopentadienone iridium complexes. The B−H bonds of 4,4,5,5‐tetramethyl‐1,3,2‐dioxaborolane (HBpin) and 1,8‐naphthalenediaminatoborane (HBdan) were cleaved to give a B anion on the metal and an H cation on the phenolic oxygen atom of the ligand. Mechanistic investigation by DFT calculations revealed that the alkox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
(9 reference statements)
0
6
0
Order By: Relevance
“…We also found that complex 1 is highly active toward the dehydrogenation of THF when we attempted to record the NMR spectrum of 1 in THF; 74% of the hydroxycyclo­pentadienyl iridium dihydride complex 3 was generated with the concomitant formation of furan when a solution of 1 in THF was kept at 60 °C for 15 h (Scheme a). This dehydrogenation activity was further applied to catalytic transfer-dehydrogenation of THF to furan in the presence of norbornene as the hydrogen acceptor (Scheme b) .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…We also found that complex 1 is highly active toward the dehydrogenation of THF when we attempted to record the NMR spectrum of 1 in THF; 74% of the hydroxycyclo­pentadienyl iridium dihydride complex 3 was generated with the concomitant formation of furan when a solution of 1 in THF was kept at 60 °C for 15 h (Scheme a). This dehydrogenation activity was further applied to catalytic transfer-dehydrogenation of THF to furan in the presence of norbornene as the hydrogen acceptor (Scheme b) .…”
mentioning
confidence: 99%
“…The key to our success is the use of an electron-deficient cyclopentadienone ligand, despite the oxidative additions of C−H bonds usually occurring at highly electron-rich metal centers. 1 We synthesized iridium complex 1 bearing an ethoxycarbonyl-substituted naphtho-fused cyclopentadienone ligand, 10 which was used in the following experimental studies (see Supporting Information (SI) section VII for the effect of the metal and substituent). The reactivity of the iridium hydride complex 1 in the cleavage of the C−H bonds of a hydrocarbon was first experimentally confirmed by the H/D exchange reaction with C 6 D 6 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis of the Ir–cyclopentadienone complexes was carried out by a modification of the procedure described by Nozaki et al Addition of 4,4′-dimethyl-2,2′-bipyridine (dmbpy) to air-stable but insoluble [(C 5 Tol 2 Ph 2 O)­IrCl] n occurs heterogeneously in methanol to generate the orange solid (C 5 Tol 2 Ph 2 O)­(dmbpy)­IrCl ( 1 ), which is indefinitely stable in air, either as a dry solid or in solution. The 1 H NMR spectrum of 1 in aprotic solvents is poorly resolved, with line broadening in the aromatic region (Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…Nozaki et al reported a class of cyclopentadienone–iridium complexes bearing phosphine ligands that catalyze hydrogenation and dehydrogenation reactions between 150 and 200 °C. Related Cp*­(bpy)­IrH + complexes are efficient catalysts for transfer hydrogenation in water at low pH. In organic solvents, Cp*­(bpy)­IrH + is unreactive toward aldehydes, which was attributed to the modest hydride donating ability (Δ G H‑(MeCN) ≥ 60 kcal/mol) of these cationic Ir hydrides. , However, in the presence of visible light, Cp*­(bpy)­IrH + complexes are effective in hydride transfer reactions, as the hydride donating ability is enhanced by photoexcitation. , We sought to test the hypothesis that modestly hydridic cationic Ir hydrides bearing hydroxycyclopentadienyl ligands might be more generally reactive toward polar substrates in nonaqueous conditions due to bifunctional activation.…”
Section: Introductionmentioning
confidence: 99%